Evaluación de las estrategias de ingreso de Colombia al Foro de Cooperación Económica Asia-Pacífico (APEC) (2016)
Given that the foreign policy of countries and international relations themselves are dynamic, each country prioritizes short-, medium- and long-term objectives that are instrumented in its International Insertion Strategy. Colombia has not been alien to this dynamic, and after establishing such priorities and objectives for the achievement of it and articulated to the objectives and instruments of trade policy, as a tool of the Colombian Economic Policy translated into Trade Agreements, Free Trade Agreements Trade, Economic Partnership Agreements, etc.